If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11.6h + 11.55 = -12.7h Reorder the terms: 11.55 + -11.6h = -12.7h Solving 11.55 + -11.6h = -12.7h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '12.7h' to each side of the equation. 11.55 + -11.6h + 12.7h = -12.7h + 12.7h Combine like terms: -11.6h + 12.7h = 1.1h 11.55 + 1.1h = -12.7h + 12.7h Combine like terms: -12.7h + 12.7h = 0.0 11.55 + 1.1h = 0.0 Add '-11.55' to each side of the equation. 11.55 + -11.55 + 1.1h = 0.0 + -11.55 Combine like terms: 11.55 + -11.55 = 0.00 0.00 + 1.1h = 0.0 + -11.55 1.1h = 0.0 + -11.55 Combine like terms: 0.0 + -11.55 = -11.55 1.1h = -11.55 Divide each side by '1.1'. h = -10.5 Simplifying h = -10.5
| -9.1c+19.02=-14.3c+11.74 | | 21x-8=5(4x+5)-17 | | -5(r+2)=81 | | -1/2q-4=9 | | 20+4y=40 | | 5(10-2n)=70 | | 8(x+15)=7 | | 1/5q-49 | | 6(2g-1)=13 | | 4(g+4)=2(4-g) | | 4x+4=7y | | 4y+4=7y | | 1/3x10=55 | | -4(3x-7)=-12x-28 | | 5x+15=3(x+5) | | 112x=245x+95 | | 5.5=7.9-0.6x | | x-41=70 | | 7=-x+264 | | y+51=89 | | -37-8= | | h(t)=-16t^2+20t+17 | | x(x+3)-5=3x+20 | | 3x+7-5(x+1)=2x+5 | | 5y+3y-5=6(4y+3) | | -4s+9=-24 | | 2r+4=-16 | | (6+9)x=15x | | 10z^2+17z-20= | | 8y-12y+9=24-y | | 120-x=3x | | 3(r+1)-1[2(3-2r)-3(3-r)]=2(r+5)-4 |